The role of physical activity, diet, and stress management in maternal and infant health during pregnancy - Bartosz Pawłowski; Aleksandra Madej; Karolina Haczkur-Pawłowska; Kacper Jasiński; Alicja Kowal; Julia Malczewska; Kornelia Fiszer; Aleksandra Łomża-Łaba; Stanisław Dziurda; Grzegorz Jama (Quality in Sport)
Introduction and aim of the study: During pregnancy, significant physiological, hormonal and circulatory changes occur that affect both the health of the mother and the child. Therefore, it is important for the mother to maintain physical activity, a healthy diet, and reduce stress to prevent complications and health problems for the mother and the child.